Preparation and Performance Evaluation of Plant Protein-Based Maize Yellow Pigment Microcapsules - GAO Li, YANG Junyan, ZHAO Yinghu, JI Haixia, CHEN Jiahui, HAO Yuan, SHI Ying, HAO Rui (Shipin Kexue)
To overcome the problems associated with maize yellow pigment (MYP) such as poor water solubility, instability, and low bioavailability, MYP was microencapsulated with different plant-based proteins, pea protein isolate (PPI), hemp protein (HP), or soybean protein isolate (SPI) combined with sodium alginate (SA) as a mixed wall materials or maltodextrin as a single wall material. The encapsulation efficiency, physicochemical properties, particle size, thermal stability, microstructure, in vitro digestion characteristics, and antioxidant capacity of the microcapsules were evaluated, and their protective effect on H2O2-induced oxidative damage in ARPE-19 cells was investigated. The results showed that microencapsulation of MYP improved its solubility, bioavailability and antioxidant activity. Microcapsules with MYP concentrations in the range of 375–1 125 μg/mL did not affect the viability of ARPE-19 cells, and showed superior cellular antioxidant effect in the H2O2-induced oxidative damage model. The three mixed wall materials exhibited different functional characteristics. Compared with those prepared with the other wall materials, PPI-SA microcapsules showed higher encapsulation efficiency, lower water content, smaller particle size, and better fluidity and stability.